Sosialisasi Pendidikan Terkait Pemahaman Demokrasi terhadap Anak Usia Dini di Desa Taman Kecamatan Jrengik Kabupaten Sampang - Raka Satya Dwiantama; Sumriyah Sumriyah (Institut Teknologi dan Bisnis Semarang, 2024)
Democracy is a system carried out in government where all people participate in governing and governing their country through the intermediary of the people's representatives. This service is entitled